Sistem Informasi Geografis untuk Pemilihan Lokasi Terdekat ATM pada Wilayah Kecamatan Wonomulyo Berbasis Web - Muh Sadik; Reski Idrus; Basri Basri; Noer Ekafitri Sam (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
This research focuses on the creation and implementation of a web-based Geographic Information System (GIS) to map the position of Automated Teller Machines (ATMs) in Wonomulyo District, Polewali Mandar Regency. The rationale behind this research is rooted in the rapid economic and demographic development in the area, which requires easy access to financial services. However, the distribution of existing ATM points is still uneven, where people in rural areas often have to travel long distances to reach the nearest ATM. The method of creating this system involves the use of the PHP programming language along with a MySQL database. This system aims to present spatial information about the current ATM location accurately, thereby helping the public in finding banking services with high accuracy through an interactive map interface. In addition, this system offers optimal paths to ATM locations to improve user time efficiency. System evaluation was conducted using black box techniques to verify that the menu operations and application procedures function as intended. The findings indicate that the implementation of GIS improves public access while offering data assistance for financial institutions and local governments in developing a more equitable and systematic public facility allocation strategy in the future.